2016
DOI: 10.1186/s40064-016-3304-0
|View full text |Cite
|
Sign up to set email alerts
|

Laying performance, digestibility and plasma hormones in laying hens exposed to chronic heat stress as affected by betaine, vitamin C, and/or vitamin E supplementation

Abstract: Heat stress had a negative effect on laying hens’ performance, thus this research was to study the influences of betaine (Bet, 1000 mg/kg betaine), vitamin C (VC, 200 mg/kg ascorbic acid), and vitamin E (VE, 150 mg/kg α-Tocopherol acetate) and their possible combinations on egg production, digestibility of nutrients, plasma hormones and reproductive organs of dual-purpose hens exposed to chronic heat stress. Two hundred and eighty eight hens and thirty-six cocks from 32 to 48 weeks of age were divided into nin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

14
92
0
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 125 publications
(123 citation statements)
references
References 40 publications
(58 reference statements)
14
92
0
2
Order By: Relevance
“…In this study, supplementation with resveratrol showed an increasing trend on the GLU and TP content, while TC, TG, and UA contents in serum were decreased, especially supplementation with resveratrol 500 mg/kg. Decreased serum GLU and TP are known to be a limiting factor for animal growth (Attia et al., ), and that was consistent with what we observed in our data of lower growth performance, but the gap was narrowed down by resveratrol supplementation. Liu et al.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…In this study, supplementation with resveratrol showed an increasing trend on the GLU and TP content, while TC, TG, and UA contents in serum were decreased, especially supplementation with resveratrol 500 mg/kg. Decreased serum GLU and TP are known to be a limiting factor for animal growth (Attia et al., ), and that was consistent with what we observed in our data of lower growth performance, but the gap was narrowed down by resveratrol supplementation. Liu et al.…”
Section: Discussionsupporting
confidence: 92%
“…Besides these meta- (Luo et al, 2018). Attia et al (2016) also found that heat stress significantly decreased serum GLU content of laying hens.…”
Section: Discussionmentioning
confidence: 84%
See 1 more Smart Citation
“…The earlier studies are inconclusive with regard to the correlation between the VE and laying performance. An increase in the VE content of hen diets from 20–25 IU/kg to 60–65 IU/kg significantly improved daily egg production (Kirunda, Scheideler, & Mckee, ), while even high dietary concentrations of VE (100 and 200 IU/kg) did not increase egg production, as compared with non‐supplemented diets and diets supplemented with a low (20 IU/kg) amount of VE (Attia et al, ; Mohiti‐Asli, Shariatmadari, & Lotfollahian, ). In the present study, VE did not significantly improved egg production performance.…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, dietary betaine supplementation was also shown to improve the digestibility of CP (Ezzat et al, 2011;Attia et al, 2016) and EE in laying chickens (Ezzat et al, 2011). Moreover, studies with broilers have revealed that betaine improved DM (Ratriyanto et al, 2014a;Amerah & Ravindran, 2015), OM (El-Husseiny et al, 2007), CP,…”
Section: Nutrient Digestibilitymentioning
confidence: 99%